PROGRAMA NACIONAL DE EDUCAÇÃO DO CAMPO (PRONACAMPO): entre a pauta dos povos do campo e o decidido pelo Estado - Moraes, Vitor de (2014)
The research that guided this study aimed to understand what epistemological, philosophical, theoretical and methodological principles of the Field Education foundations are in confrontation in the National Rural Education (Pronacampo), the correlation of forces between different social segments in the drafting process of this program and interests in the share of international organizations, expressed in education policy of the federal government. This investigation aims to signal leaps and bounds toward satisfaction of the desires of Social Movements of the field and indicate the existing configuration of a public health policy limits. Indicate the theoretical framework. This research aligns with dialectical historical materialism, by considering how a complete method to explain the history, the contradictions, mediations regarding the dialectical movement of reality in its entirety. The methodological procedure to bring the whole, addresses from the empirical, with interviews, document studies, mediations do with other empirical sets, investigating its historical genesis and its internal development and rebuilding, in terms of abstraction and construction of knowledge, this whole process. The analysis allows us to understand the tensions that existed in the development and launch of Pronacampo between different field projects and Rural Education. Advances and contradictions within the concept itself at the same time, the possibility of collective social movements and researchers, reflect on their practice, under the law, politics and utopia emancipation. For both the debate expands, around how the unique and global reality can be connected by the Field Education, in order to contribute to the proposal for an education that instigates human subjects and political emancipation and the overcoming of backwardness and dichotomy city field. The Pronacampo, in principle, does not represent the anxieties of Popular Social Movements of the field.